2013
DOI: 10.1108/00368791311303438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of roller burnishing on pure aluminum alloyed by copper

Abstract: Purpose -The purpose of this paper is to review, analyze and present the effects of the roller burnishing process on pure aluminum alloyed by pure copper at 3%, 6% and 9% percentages. Roller burnishing is one of the effective finishing treatment methods in terms of stabilization of surface layers properties along the depth, Roller burnishing is one of the effective methods used to improve the surface layer properties such as microhardness and average surface roughness. Design/methodology/approach -Three differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The internal roller burnishing tool was used to burnish the drilled hole in the plain carrier of planetary-type gear box. The investigations were carried out by varying speed, feed, and number of passes using Taguchi method to examine the microhardness and surface finish [16] From the above literature, it was found that a potential area of research was available in the area of superfinishing process especially by burnishing. A few work has been carried out in industry component.…”
Section: Introductionmentioning
confidence: 99%
“…The internal roller burnishing tool was used to burnish the drilled hole in the plain carrier of planetary-type gear box. The investigations were carried out by varying speed, feed, and number of passes using Taguchi method to examine the microhardness and surface finish [16] From the above literature, it was found that a potential area of research was available in the area of superfinishing process especially by burnishing. A few work has been carried out in industry component.…”
Section: Introductionmentioning
confidence: 99%
“…The workpiece was cylindrical in shape. Burnishing operation was applied at different conditions and the results were investigated by Al Qawabeha and Al Qawabah [2]. Qureshi et al [16] investigated ball and roller burnishing processes on EN8 steel by varying burnishing parameters like speed, feed, depth of cut and number of passes on surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review has shown that numerous experimental studies have been conducted to identify the effects of burnishing on surface quality and surface microhardness. Surface roughness, after ball burnishing treatment, can be improved by 40% to 90%, while hardness can be increased by 5% to 160% [16,19]. A multi-objective optimization of process parameters for low plasticity burnishing on aluminum alloy AA6061T6 was performed by Thorat et al [20].…”
Section: Introductionmentioning
confidence: 99%